The Neural Bases of Interoceptive Encoding and Recall in Healthy and Depressed Adults. - DeVille, Danielle C. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2018)
BACKGROUND: Theoretical models assert that the brain’s interoceptive network links external stimuli with their interoceptive consequences, thereby supporting later recall of these associations to guide the selection of healthy behaviors. If these accounts are correct, previously reported interoceptive abnormalities in major depressive disorder (MDD) should lead to altered recall of associations between external stimuli and their interoceptive (somatic) consequences. To date, the processes underlying interoceptive recall have never been experimentally investigated. METHODS: We designed and implemented the Interoceptive Encoding and Recall (IER) task to compare interoceptive and exteroceptive recall among MDD (n=24) and healthy comparison subjects (n=21). During the encoding phase, subjects learned to pair neutral visual cues (geometric shapes) with aversive interoceptive and exteroceptive stimuli. Later, while undergoing fMRI, subjects were prompted to recall the stimulus associated with each shape. RESULTS: Interoceptive recall, relative to exteroceptive recall, was associated with bilateral mid-to-posterior insula activation. Relative to the healthy controls, depressed participants exhibited marked hypo-activation of the right dorsal mid-insula during interoceptive recall. CONCLUSIONS: In non-depressed subjects, simply recalling a stimulus associated with a previous interoceptive challenge activated a key region in the brain’s interoceptive network. Although previous research has linked MDD with aberrant processing of interoceptive stimuli, the current study is the first to demonstrate that individuals with MDD exhibit decreased insula activity while recalling interoceptive memories. It is possible that insula hypo-activation during interoceptive recall may affect the representation of prior interoceptive experiences in ways that contribute to depressive symptomology and the relationship between depression and systemic health.